Anticancer, Nutritional & Other Therapeutic Potentials of Microgreens - Kanwaljit Singh; Mukesh Chander (Emerging Trends in Metabolites, 2026)
Microgreens are young, tender greens, immature greens (require light for photosynthesis and growing medium) that are developed from the seeds of cereals, herbs, legumes, and vegetables. These are used to enhance the color, texture, or flavor of salads and main dishes. The immature plants are harvested between 7 and 21 days, depending on the variety. They are referred to as "living superfoods," "functional foods," or "nutraceuticals," because they are rich in minerals (Ca, Mg, Fe, Mn, Zn, Cu, Se, and Mo), vitamins (like vitamin C), β-carotene, chlorophyll, lutein, and phytochemicals (like carotenoids and phenolic compounds), which act as antioxidants in the human body. Pre-harvest practices that affect microgreens' metabolic and photosynthetic processes and enhance nutritional value include nutrient fortification, natural substrates, lighting, and salinity stress. From straightforward home gardens to intricate vertical farms with computerized lighting controls, fertilizer supply, and irrigation, they can be grown in a variety of setups. These characteristics have drawn interest from researchers studying their application in human nutrition and health, and they may help prevent chronic diseases, including inflammation and malnutrition. For cultivating microgreens on and beyond Earth, there are still a lot of unresolved technical issues and data shortages. Recent research on microgreens, including their nutritional and socioeconomic advantages, growth methods, operating environments, novel treatments, self-sufficient facilities, and possible space applications, is compiled in this review paper.
Keywords: Microgreens; Superfoods; anticancer; biofortification; nutraceuticals